Lymphocytic Choriomeningitis Virus Infection Demonstrates Higher Replicative Capacity and Decreased Antiviral Response in the First-Trimester Placenta - Elizabeth Ann L. Enninga; Regan N. Theiler (Journal of Immunology Research)
Lymphocytic choriomeningitis virus (LCMV) is a rodent disease that can be transmitted to humans. A majority of persons infected with LCMV have only minor symptoms; however, it can cross the placental barrier during pregnancy and cause congenital defects in the fetus. Some viral infections early in gestation are hypothesized to lead to worse outcomes compared to those acquired during late gestation; however, LCMV has not been studied in this context. In the present study, differences in immunomodulation between the first- and third-trimester placental explants infected with LCMV were measured. LCMV replication was observed in the first-trimester chorionic villi, but not in term. The term placenta exhibited a robust innate immune response to infection by LCMV, marked by induction of ifn-α, il-6, and tnf-α gene expression which was not seen in the first-trimester explants. Cytokine secretion was also only seen in term explants. The results indicate that the first-trimester and term placentas differ in their permissiveness for LCMV infection, inversely correlating with the innate antiviral responses. This has implications for developing effective mechanisms that protect the fetus from infection based on stage of development.